Performance of Some Tomato (Solanum lycopersicum L.) Genotypes in Summer and Winter Seasons - Patwary, M M Alam; Rahman, M Mizanur; Ahmad, Shahabuddin; Miah, M A Khaleque; Rahman, M H (The Agriculturists, 2015)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> An experiment was conducted at the Vegetable Research Field of Olericulture Division, Horticulture Research Centre, Bangladesh Agricultural Research Institute, Gazipur during October 2006 to March 2007 and May to September 2007 to evaluate the performance of tomato (Solanum lycopersicum) genotypes in summer and winter seasons. Early flowering was observed in summer compared to winter. Pollen viability decreased greatly during summer ranging from 30.44 % in TMS 003 to 86.08 % in C 11 compared to that in winter (70.33 % in C 61 to 100.00 % in VRT 002). Fruit set (%) markedly decreased in summer, which ranged from 4.69 % in TMS 017 to 39.15 % in C 51 while it ranged from and 49.00 % in TMS 008 to 90.01 % in HT 017 during winter. During summer, fruit set (%) exhibited positive significant and correlation with viable pollen grains (%). Yield per plant ranged from 1224 g in C 61 to 2670 g in VRT 003 and 37 g in TMS 015 to 94 g in C 11 in winter. The genotypes HT 019, C 11, C 21, C 41, C 51, HT 016 and HT 017 exhibited a considerable heat tolerance in relation to fruit setting ability. <span style="font-size: 12.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Agriculturists <span style="font-size: 12.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2014; 12(2) <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">64<span style="font-size: 12.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">-<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">73<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>